2006
DOI: 10.1111/j.1541-4329.2006.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Knowledge and Attitudes Using Computer‐based and Face‐to‐Face Personal Hygiene Training Methods in Food Processing Facilities

Abstract: Computer-based training is increasingly favored by food companies for training workers due to convenience, self-pacing ability, and ease of use. The objectives of this study were to determine if personal hygiene training, offered through a computer-based method, is as effective as a face-to-face method in knowledge acquisition and improved attitude toward food safety. Employees from four food processing facilities (n = 94) were randomly assigned to a control group, a face-to-face training group, or a computer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…However, these studies may pose various challenges to Hedges's g trainers and researchers. Fenton et al (23) found that seasonal employees in the farming and food industry were more difficult to train because of rapid employee turn over. Pilling et al (53) also faced a similar problem when food service establishments declined to participate because of the long time frame and the intrusiveness of data collection.…”
Section: Discussionmentioning
confidence: 98%
“…However, these studies may pose various challenges to Hedges's g trainers and researchers. Fenton et al (23) found that seasonal employees in the farming and food industry were more difficult to train because of rapid employee turn over. Pilling et al (53) also faced a similar problem when food service establishments declined to participate because of the long time frame and the intrusiveness of data collection.…”
Section: Discussionmentioning
confidence: 98%
“…This prior training contact was essential and was recommended by Fenton, LaBorde, Radhakrishna, Brown, and Cutter (2006). On the day of training, the participating farms' employees were immediately trained and then completed the post-training questionnaire.…”
Section: Pre-and Post-training Questionnairesmentioning
confidence: 99%
“…Most of these studies describe the program implementation or training strategies utilized, but do not focus on program evaluation (Boccas et al, 2001;Fenton, 2005;Gall et al, 2004;Harris, Marks, Ten Eyck, Booren, & Ryser, 2004;Hicks et al, 2004;Rushing, Angulo, & Beuchat, 1996). In contrast, several studies conducted within the foodservice and hospitality industries have evaluated pre-and immediate post-intervention knowledge and selfreported behaviors among workers who have attended food safety workshops (Capunzo et al, 2005;Costello, Gaddis, Tamplin, & Morris, 1997;Ehiri et al, 1997;Hennum, Lawrence, & Snyder, 1983;Kirby & Gardiner, 1997;Martin, Knabel, & Mendenhall, 1999;McElroy & Cutter, 2004;Rennie, 1994;Smith & Shillam, 2000).…”
Section: Introductionmentioning
confidence: 99%